Involvement of the Matrix and Nucleocapsid Domains of the Bovine Leukemia Virus Gag Polyprotein Precursor in Viral RNA Packaging - Wang, Huating (American Society for Microbiology, 2003)
The RNA packaging process for retroviruses involves a recognition event of the genome-length viral RNA by the viral Gag polyprotein precursor (PrGag), an important step in particle morphogenesis. The mechanism underlying this genome recognition event for most retroviruses is thought to involve an interaction between the nucleocapsid (NC) domain of PrGag and stable RNA secondary structures that form the RNA packaging signal. Presently, there is limited information regarding PrGag-RNA interactions involved in RNA packaging for the deltaretroviruses, which include bovine leukemia virus (BLV) and human T-cell leukemia virus types 1 and 2 (HTLV-1 and -2, respectively). To address this, alanine-scanning mutagenesis of BLV PrGag was done with a virus-like particle (VLP) system. As predicted, mutagenesis of conserved basic residues as well as residues of the zinc finger domains in the BLV NC domain of PrGag revealed residues that led to a reduction in viral RNA packaging. Interestingly, when conserved basic residues in the BLV MA domain of PrGag were mutated to alanine or glycine, but not when mutated to another basic residue, reductions in viral RNA packaging were also observed. The ability of PrGag to be targeted to the cell membrane was not affected by these mutations in MA, indicating that PrGag membrane targeting was not associated with the reduction in RNA packaging. These observations indicate that these basic residues in the MA domain of PrGag influence RNA packaging, without influencing Gag membrane localization. It was further observed that (i) a MA/NC double mutant had a more severe RNA packaging defect than either mutant alone, and (ii) RNA packaging was not found to be associated with transient localization of Gag in the nucleus. In summary, this report provides the first direct evidence for the involvement of both the BLV MA and NC domains of PrGag in viral RNA packaging.